Export competitiveness - Fuel Price nexus in Developing Countries: Real or False Concern? - Roland Kangni Kpodar; Stefania Fabrizio; Kodjovi Eklou (Fondation pour les études et recherches sur le développement international (FERDI), 2019)
This paper investigates the impact of domestic fuel price increases on export growth in a sample of 77 developing countries over the period 2000-2014. Using a fixed-effect estimator and the local projection approach, we find that an increase in domestic gasoline or diesel price adversely affects real non-fuel export growth, but only in the short run as the impact phases out within two years after the shock. The results also suggest that the negative effect of fuel price increase on exports is mainly noticeable in countries with a high-energy dependency ratio and countries where access to an alternative source of energy, such as electricity, is constrained, thus preventing producers from altering energy consumption mix in response to fuel price changes.
Keywords: F10; O13; Q43; 330